KARAKTER KEWIRAUSAHAAN MASYARAKAT DALAM USAHA LADUDI KECAMATAN PARIAMAN TENGAH KOTA PARIAMAN SUMATERA BARAT - Fitrha, Rona; Natuna, Daeng Ayub; Irja, Desti (Jurnal Online Mahasiswa (JOM) Bidang Keguruan dan Ilmu Pendidikan, 2016)
Abstract: This study was motivated by curiosity about the character of the community in an effort Ladu in Kota Pariaman Central Pariaman District of West Sumatra. The research problems are lack of kreaativitas community towards making Ladu. The purpose of this study was to determine the level of Character Enterprise Business Community In Ladu in Central City Pariaman Pariaman District of West Sumatra. The population in this study were 35 trials with a sample of 20 people and sample 35 in accordance with the technique of saturated samples. Data collection instrument is a questionnaire with 149 statements and after testing 131 valid statement. Data analysis through quantitative descriptive. Presentation of the calculation of the answers obtained by the findings that the entrepreneurial character of communities in Ladu businesses in Central Pariaman District of West Sumatra Pariaman City is very high in conducting entrepreneurial activity.